“Periodos de frecuencia del sistema de siembra asociado maíz (zea mays L.) con frijol caupí (vigna unguiculata L. walp), en el bajo mayo-Tarapoto” - Tangoa Tuesta, Carlos Alberto (2006)
With the purpose of determining the best time in sow of the system associated of cornbean with characteristic agronomic desirable for Bajo Mayo the First; it put on in execution a comparative rehearsal of times of sow of corn (Marginal T-29) and bean cowpea (Chongoyape) reaching the potential maximum of yield the time of 20 days of sow of the corn on the bean T5 (F+M 20 D.S.F.) with 5 890 Kg/ha, and the variety cowpea that it obtained the average but high of weight of 100 grains (1square15) it was the T5 (F+M 15 D.S.F) with 15.98 g. being 1 598 Kg/ha respectively. The experiment in mention you takes to 1 dig in San Martín country and Region, District of Morales in a soil vertisol, fine texture, potassium and high match and with saturation of bases, the disposition of the used experiment was completely of blocks randomized, being the sow of bean cowpea for blow to a distancing of 0.80 x 0.30 m and seed of corn far blow to a distancing of 0.80 x 0.50 m being obtained a population of corn of 50 000 plants for there is. Bean a population of 41 _666 plants for there is. A fertilization was made with urea and potassium toward the soil, the application of fertilizers one carries out when the plants of corn were in the stadium 4, among the first days the cultivations of corn and bean had little adaptability; mainly far climatic factors that showed the months of March, April, May, with intense rains that harmed the development of the cultivations and the increment of plagues and illnesses. But however the sow time that reported the but high grain yield was the T6 (F+M 20 D.S.F) with 5 890 Kg/ha; being the but low yield the T2 bean monocultivo with 623 Kg/ha. The profitable economic analysis with the treatments sowed in association reports a net utility of T-6 334.71 new continued suns Ts 220.69 new suns.